Tungsten oxide film electrode material, preparation method and application thereof

By combining the tungsten oxide thin film electrode material with FTO conductive glass, a tungsten oxide thin film electrode material with excellent light absorption performance and strong oxidation ability was prepared, which solved the problem of insufficient photocatalytic performance of tungsten oxide materials and difficult to recover composite materials in the prior art, and achieved efficient and stable degradation of organic pollutants.

CN119701929AActive Publication Date: 2025-03-28EAST CHINA UNIV OF SCI & TECH
View PDF 7 Cites 0 Cited by

Patent Information

Application Number
CN202411907465.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-24
Publication Date
2025-03-28
Estimated Expiration
2044-12-24

AI Technical Summary

Technical Problem

In the prior art, when photoelectrolytic degradation of organic pollutants, the photocatalytic performance of tungsten oxide materials is insufficient, and the composite material preparation process is complex and difficult to recycle.

Method used

Using tungsten oxide thin-film electrode material, the tungsten oxide thin-film electrode material is made by dripping the ammonium metatungstate precursor solution on FTO conductive glass and dried and calcined. The material has a small energy band gap and a negative valence band potential, which improves the light absorption performance and oxidation ability.

Benefits of technology

It improves the removal efficiency of organic pollutants, has good cycle stability, and has higher catalytic degradation activity in high saline environments, solving the problem that traditional photocatalysts are difficult to recover.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119701929A_ABST
    Figure CN119701929A_ABST
Patent Text Reader

Abstract

The invention belongs to the field of functional thin film material preparation, and particularly relates to a tungsten oxide thin film electrode material, a preparation method and application thereof.The tungsten oxide thin film electrode material composed of a substrate and a tungsten oxide thin film covering the substrate is prepared by dispensing a tungsten oxide precursor solution on an FTO conductive glass substrate and drying and calcining the substrate; the material has excellent light absorption performance and strong oxidation capacity, has the advantages of strong cycle stability and strong oxidation capacity in the aspect of advanced oxidation catalytic degradation of organic pollutants, has higher catalytic degradation activity when sodium chloride is used as an electrolyte, is simple and feasible in preparation process, and is suitable for industrial production. And the method has a relatively high application prospect in the field of pollutant degradation.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of preparation of functional thin film materials, and specifically relates to a tungsten oxide thin film electrode material and a preparation method thereof, and also relates to the application of the thin film electrode material in photoelectrocatalytic degradation of organic pollutants. Background Art

[0002] With the continuous development of human society, various refractory organic pollutants, such as antibiotics, surfactants, dyes and organic pesticides, continue to accumulate in the environment and harm animals and humans. Therefore, finding efficient and practical methods to treat organic pollutants has become an important research topic in the current environmental field.

[0003] Adsorption and advanced oxidation are relatively common treatment technologies. Among them, most sewage treatment plants often use advanced oxidation processes such as Fenton oxidation and ozone oxidation, but these traditional processes have obvious defects such as low utilization of H2O2 or ozone, increased treatment costs and secondary pollution. Photoelectrocatalysis is based on the coupling of photocatalysis and electrocatalysis. It drives photogenerated electrons to the cathode through an external circuit to reduce the recombination rate of photogenerated electron-hole pairs, thereby producing more active oxygen species that can effectively remove organic pollutants. Compared with traditional pollutant treatment technologies, it has the advantages of being environmentally friendly, non-toxic, easy to operate, low-cost and high degradation efficiency. It is one of the most promising technologies for removing organic pollutants.

[0004] Tungsten oxide is a semiconductor material commonly used in the field of photocatalysis. It has a narrow bandgap width, a suitable bandgap structure, and can produce abundant reactive oxygen species. It shows great potential in the field of photoelectrocatalytic degradation of organic pollutants. The use of tungsten oxide for photoelectrocatalytic degradation of pollutants can make full use of its advantages such as low valence band potential, and can produce more reactive oxygen species to degrade pollutants. Tungsten oxide materials are easy to synthesize and do not produce secondary pollution. They are green and environmentally friendly catalysts and are expected to become ideal materials for photoelectrocatalytic removal of antibiotics. They have important theoretical and practical value in the field of environmental remediation.

[0005] Prior art, such as patent application number 202111519808.7, discloses a method for treating antibiotic wastewater using a carbon nitride / tungsten trioxide / zinc sulfide double Z-type composite photocatalyst. The antibiotic wastewater is subjected to oscillating adsorption and photocatalytic degradation treatment using a carbon nitride / tungsten trioxide / zinc sulfide double Z-type composite photocatalyst, thereby achieving effective removal of antibiotics from the wastewater. Another example of prior art, such as patent application number 201811446965.8, discloses a visible light-driven inverse opal photocatalytic material, its preparation method, and its degradation and removal of organic pollutants in water bodies, which solves the problem that the conduction band energy levels of tungsten trioxide and bismuth tungstate are too positive to generate enough reducing electrons, thereby improving the light absorption capacity of the material, accelerating the separation efficiency of electron holes, and effectively degrading pollutants.

[0006] The existing technology mostly uses tungsten oxide and other photocatalytic materials to make composite materials to improve their photocatalytic degradation performance. The preparation process is complicated and there is a problem of difficulty in recycling when in use. Summary of the invention

[0007] In view of the problems existing in the application of tungsten oxide materials, the purpose of the present invention is to provide a tungsten oxide thin film electrode material and a preparation method thereof, and to provide the application of the material in the photoelectrocatalytic degradation of organic pollutants. The tungsten oxide thin film electrode material prepared by the present invention has a smaller energy band gap and a more negative valence band potential, exhibits better light absorption performance, and its photogenerated holes have stronger oxidation ability, which improves the removal efficiency of organic pollutants through photoelectrocatalysis and has good cycle stability.

[0008] Based on the above purpose, the technical solution adopted by the present invention is as follows:

[0009] In a first aspect, the present invention provides a tungsten oxide thin film electrode material, which consists of a substrate and a tungsten oxide thin film covering the substrate; wherein the substrate is FTO conductive glass; and the thickness of the tungsten oxide thin film is 110-120 μm.

[0010] Preferably, the oxide thin film electrode material is an n-type semiconductor, the band gap width of the oxide thin film electrode material is 2.54 to 2.62 eV, and the valence band position is 2.50 to 2.62V.

[0011] The present invention combines tungsten oxide with a conductive substrate for the first time to prepare a tungsten oxide thin film electrode material. The prepared tungsten oxide thin film electrode material has excellent light absorption performance and strong oxidation ability, and has efficient photoelectric catalytic degradation ability for norfloxacin (NOR). At the same time, the prepared tungsten oxide thin film electrode material has stable properties and can be recycled for a long time. It has more excellent degradation performance when sodium chloride is used as an electrolyte, and has important application value and application prospects in the degradation of organic pollutants.

[0012] In a second aspect, the present invention provides a method for preparing the above-mentioned tungsten oxide thin film electrode material, comprising the following steps:

[0013] S1: dissolving ammonium metatungstate in a solvent, adding citric acid aqueous solution and Triton X-100 thereto, and stirring to obtain a precursor solution;

[0014] S2: drop the precursor solution onto the restricted area of ​​FTO conductive glass, dry it at room temperature and then calcine it to obtain tungsten oxide thin film electrode material.

[0015] The present invention is very simple to prepare tungsten oxide thin film electrode materials, and does not require complex synthesis methods such as electrodeposition and hydrothermal. The present invention adopts the method of drop-coating an ammonium metatungstate precursor solution on FTO conductive glass, followed by drying and calcination to prepare tungsten oxide thin film electrode materials. The prepared electrode material has a smaller energy band gap and a more negative valence band potential, has better light absorption performance, and its photogenerated holes have stronger oxidation ability, and has stronger catalytic degradation performance for organic pollutants.

[0016] Preferably, the dosage ratio of ammonium metatungstate to citric acid aqueous solution in the precursor solution is 0.2 g:0.12 mL; and the concentration of the citric acid aqueous solution is 0.1-5M.

[0017] Adding citric acid can make tungsten oxide have a better morphology. When the amount of citric acid aqueous solution in the reaction system is within the above addition range relative to ammonium metatungstate, the prepared product has better photoelectric conversion performance.

[0018] Preferably, the dosage ratio of ammonium metatungstate to Triton X-100 in the precursor solution is 0.2 g:10 μL.

[0019] The purpose of adding Triton X-100 to the reaction system is to enhance the hydrophilicity and film-forming property of the precursor solution on the FTO glass substrate. When the amount of Triton X-100 in the reaction system is 10 μL:0.2 g relative to the amount of ammonium metatungstate added, the prepared product has better stability.

[0020] Preferably, the solvent is an ethanol aqueous solution, and the volume fraction of ethanol in the ethanol aqueous solution is 37.5%.

[0021] Preferably, in step S2, the amount of the precursor solution dripped into the FTO conductive glass confinement area is 50 μL.

[0022] Preferably, the calcination parameters in step S2 are as follows: heating to 550° C. at a heating rate of 1° C. / min and calcining for 2 h.

[0023] In a third aspect, the present invention provides the use of the above-mentioned tungsten oxide thin film electrode material in the degradation of organic pollutants in a high-salt water environment.

[0024] Preferably, the salt water concentration in the high salt water environment is 0.05-1 M; and the organic pollutants include norfloxacin.

[0025] Compared with the prior art, the present invention has the following beneficial effects:

[0026] The present invention combines tungsten oxide with a conductive substrate for the first time to form a tungsten oxide thin film electrode material. The prepared tungsten oxide thin film electrode material has excellent light absorption performance and strong oxidation ability. It has the advantages of strong cycle stability and strong oxidation ability in advanced oxidation catalytic degradation of organic pollutants. At the same time, it has higher catalytic degradation activity when sodium chloride is used as the electrolyte, and has high application prospects in the field of pollutant degradation.

[0027] The tungsten oxide thin film electrode material preparation process of the present invention is simple and easy. By preparing tungsten oxide into a thin film electrode, the problem of the difficulty in recycling traditional photocatalysts is solved, and it can be recycled efficiently. For the tungsten oxide material itself, the bias voltage can be used to improve its photogenerated carrier separation ability, and the electrolyte present in the water environment can be used, so that it can be better applied to the treatment of organic pollutants. BRIEF DESCRIPTION OF THE DRAWINGS

[0028] Figure 1 The transient photocurrent response diagram of the tungsten oxide thin film electrode materials obtained in Examples 1 to 4 and Comparative Examples 1 to 3;

[0029] Figure 2 XRD and Rman diagram of the product of Example 1;

[0030] Figure 3 is the SEM image of the product of Example 1;

[0031] Figure 4 TEM and HREM images of the product of Example 1;

[0032] Figure 5 is the UV-visible diffuse reflectance spectrum of the product of Example 1, (αhν) 1 / 2 with hν diagram, XPS valence band diagram and Mott-Schottky plot;

[0033] Figure 6 The photoelectrocatalytic degradation activity diagram of norfloxacin of the product of Example 1;

[0034] Figure 7 The photoelectrocatalytic degradation activity diagram of norfloxacin by the product of Example 1 under the influence of different voltages;

[0035] Figure 8This is a cycle test diagram of the photoelectrocatalytic degradation of norfloxacin by the product of Example 1;

[0036] Fig. 9 This is the activity diagram of the product of Example 1 in degrading NOR in different electrolytes. DETAILED DESCRIPTION

[0037] In order to better illustrate the purpose, technical scheme and advantages of the present invention, the present invention will be further described below in conjunction with specific embodiments. It should be understood by those skilled in the art that the specific embodiments described herein are only used to explain the present invention and are not intended to limit the present invention. The test methods used in the examples are conventional methods unless otherwise specified; the materials, reagents, etc. used can be obtained from commercial sources unless otherwise specified.

[0038] Example 1

[0039] This embodiment provides a method for preparing a tungsten oxide thin film electrode, comprising the following steps:

[0040] 0.2 g of ammonium metatungstate hydrate was dissolved in a mixture of 1.0 mL of water and 0.6 mL of ethanol, and ultrasonicated for 15 min. Then, 0.12 mL of 1 M citric acid aqueous solution and 10 μL of Triton X-100 were added. After stirring at room temperature for 60 min, 50 μL was dropped on a 2*2 cm thick FTO conductive glass. 2 After drying at room temperature, the sample was placed in a muffle furnace and heated to 550°C at a heating rate of 1°C / min for 2 h. After cooling to room temperature, a tungsten oxide thin film electrode material was obtained, which was recorded as WO3-1:10.

[0041] Example 2

[0042] 0.2 g of ammonium metatungstate hydrate was dissolved in 1.0 mL of water and 0.6 mL of ethanol, and ultrasonicated for 15 min. Then, 0.12 mL of 0.1 M citric acid aqueous solution and 10 μL of Triton X-100 were added. After stirring at room temperature for 60 min, 50 μL was dropped on the FTO conductive glass with a size of 2*2 cm. 2 After drying at room temperature, the sample was placed in a muffle furnace and heated to 550°C at a heating rate of 1°C / min for 2 h. After cooling to room temperature, a tungsten oxide thin film electrode material was obtained, which was recorded as WO3-0.1:10.

[0043] Example 3

[0044] Dissolve 0.2 g of ammonium metatungstate hydrate in 1.0 mL of water and 0.6 mL of ethanol, sonicate for 15 min, then add 0.12 mL of 0.5 M citric acid aqueous solution and 10 μL of Triton X-100, stir at room temperature for 60 min, and then take 50 μL and drop it on the FTO conductive glass 2*2 cm2 After drying at room temperature, the sample was placed in a muffle furnace and heated to 550°C at a heating rate of 1°C / min for 2 h. After cooling to room temperature, a tungsten oxide thin film electrode material was obtained, which was recorded as WO3-0.5:10.

[0045] Example 4

[0046] 0.2 g of ammonium metatungstate hydrate was dissolved in 1.0 mL of water and 0.6 mL of ethanol, and ultrasonicated for 15 min. Then, 0.12 mL of 5 M citric acid aqueous solution and 10 μL of Triton X-100 were added. After stirring at room temperature for 60 min, 50 μL was dropped on the FTO conductive glass with a size of 2*2 cm. 2 After drying at room temperature, the sample was placed in a muffle furnace and heated to 550°C at a heating rate of 1°C / min for 2 h. After cooling to room temperature, a tungsten oxide thin film electrode material was obtained, which was recorded as WO3-5:10.

[0047] Comparative Example 1

[0048] The only difference between this comparative example and Example 1 is that no citric acid aqueous solution and Triton X-100 are added, and the prepared product is recorded as WO3-0:0.

[0049] The specific preparation method of WO3-0:0 is as follows:

[0050] Dissolve 0.2g of ammonium metatungstate hydrate in a mixture of 1.0mL of water and 0.6mL of ethanol, ultrasonicate for 15min, stir at room temperature for 60min, and then take 50μL and drop it on the FTO conductive glass with a size of 2*2cm. 2 After drying at room temperature, the sample was placed in a muffle furnace and heated to 550°C at a heating rate of 1°C / min for 2 hours. After cooling to room temperature, a tungsten oxide thin film electrode material WO3-0:0 was obtained.

[0051] Comparative Example 2

[0052] The only difference between this comparative example and Example 2 is that Triton X-100 is not added, and the prepared product is recorded as WO3-0.1:0.

[0053] The specific preparation method of WO3-0.1:0 is as follows:

[0054] Dissolve 0.2 g of ammonium metatungstate hydrate in 1.0 mL of water and 0.6 mL of ethanol, sonicate for 15 min, then add 0.12 mL of 0.1 M citric acid aqueous solution, stir at room temperature for 60 min, take 50 μL and drop it on the FTO conductive glass 2*2 cm 2After drying at room temperature, the sample was placed in a muffle furnace and heated to 550°C at a heating rate of 1°C / min for 2 hours. After cooling to room temperature, a tungsten oxide thin film electrode material WO3-0.1:0 was obtained.

[0055] Comparative Example 3

[0056] The only difference between this comparative example and Example 1 is that no citric acid aqueous solution is added, and the prepared product is recorded as WO3-0:10.

[0057] The specific preparation method of WO3-0:10 is as follows:

[0058] Dissolve 0.2g of ammonium metatungstate hydrate in a mixture of 1.0mL of water and 0.6mL of ethanol, sonicate for 15min, then add 10μL of Triton X-100, stir at room temperature for 60min, take 50μL and drop it on a 2*2cm thick FTO conductive glass. 2 After drying at room temperature, the sample was placed in a muffle furnace and heated to 550°C at a heating rate of 1°C / min for 2 hours. After cooling to room temperature, a tungsten oxide thin film electrode material WO3-0:10 was obtained.

[0059] The transient photocurrent response diagrams of the tungsten oxide thin film electrode materials obtained in Examples 1 to 4 and Comparative Examples 1 to 3 are shown in FIG. Figure 1 As shown in Figure 1, the addition of citric acid and Triton X-100 to the tungsten oxide thin film electrode material can significantly enhance its photocurrent intensity. The tungsten oxide thin film electrode material prepared when the citric acid concentration is 1M (Example 1) has the best photoelectric conversion performance. In a 0.5M Na2SO4 electrolyte solution, 100mM / cm 2 At a light intensity of 1.5 mA / cm and a bias voltage of 1.23 V (vs. RHE), it can generate 1.5 mA / cm 2 The photocurrent is about .

[0060] The XRD and Raman patterns of the product obtained in Example 1 are as follows: Figure 2 As shown by Figure 2 It can be seen that the appearance of (002) and (200) crystal planes indicates that monoclinic tungsten oxide has been successfully synthesized, and the characteristic peaks appearing in the Raman spectrum match well with the monoclinic WO3, indicating that the synthesized WO3 has good crystallinity.

[0061] The SEM image of the product obtained in Example 1 is as follows Figure 3 As shown by Figure 3 It can be seen that the prepared tungsten oxide film exists mainly in the form of irregular nanoplates on the FTO substrate, and its thickness is about 115 μm.

[0062] The TEM and HRTEM images of the product of Example 1 are as follows: Figure 4As shown, it can be seen from the TEM image that tungsten oxide presents a nanoplate structure similar to the SEM image, and the lattice fringes belonging to the (002) and (200) crystal planes of tungsten oxide can be observed in the HRTEM image.

[0063] Figure 5 is the UV-visible diffuse reflectance spectrum of the product of Example 1, (αhν) 2 With hν diagram, XPS valence band diagram and Mott-Schottky curve diagram. Figure 5 It can be seen that the tungsten oxide thin film electrode belongs to an n-type semiconductor with a band gap of 2.58eV. After analysis and calculation, its valence band position is 2.56V. It can be seen that the prepared tungsten oxide thin film electrode material has a suitable band gap and a lower valence band position, which is conducive to enhancing the oxidation ability of holes and increasing the concentration of active oxygen species.

[0064] The photoelectrocatalytic performance of the material in Example 1 is compared with that of the prior art, as shown in Table 1. Without loading other catalyst materials, WO3-1:10 has a bias voltage of 1.23 V (vs. RHE) and a photoelectrocatalytic performance of 100 mW / cm 2 1.5mA / cm can be achieved under light intensity 2 The photocurrent density is better than that of most tungsten oxide composite catalysts, which means that the tungsten oxide thin film electrode material prepared by the present invention has better photoelectrocatalytic performance.

[0065] Table 1

[0066]

[0067]

[0068] Note: The references cited in [1] to

[10] in Table 1 are as follows:

[0069] [1] Qingyi Zeng, Jinhua Li, Jing Bai, Xuejin Li, Ligang Xia, Baoxue Zhou, Preparation of vertically aligned WO3 nanoplate array films based on peroxotungstate reduction reaction and their excellent photoelectrocatalytic performance, Applied Catalysis B: Environmental 202 (2017) 388-396.

[0070] [2]U.Prasad,J.Prakash,SKGupta,J.Zuniga,Y.Mao,B.Azeredo,ANMKannan,ACSApplMater Interfaces,11(2019)19029-19039.

[0071] [3]S.Bai,X.Yang,C.Liu,X.Xiang,R.Luo,J.He,A.Chen,ACS SustainableChemistry&Engineering,6(2018)12906-12913.

[0072] [4]X.Fan,T.Wang,H.Xue,B.Gao,S.Zhang,H.Gong,H.Guo,L.Song,W.Xia,J.He,ChemElectroChem,6(2019)543-551.

[0073] [5]Xiubing Huang,Guixia Zhao,and Ge Wang,Sub-nano CoO x attached ontoWO3 for efficient photocatalytic and photoelectrochemical water oxidation,J.Mater.Chem.A,2017,5,24631.

[0074] [6]J.Huang,Y.Ding,X.Luo,Y.Feng,J.Catal.2016,333,200.

[0075] [7]J.Ji,P.Sang,JHKim,Ceram.Int.2021,47,26260.

[0076] [8]P.Sang,JHKim,Int.J.Precis.Eng.Manuf.-GreenTechnol.2023,10,1015.

[0077] [9] Weihao Wu, Zhehui Yan, Lijun Wang, Xiangrong Zhu, Yongheng Zhu, Guihong Liao, and Luping Zhu, Efficient WO3 Nanoplate Arrays Photoanode Modified by ZnO Nanosheets for Enhanced Charge Separation and Transfer to Promote Photoelectrochemical Performances, Adv. Electron. Mater. 2024, 10, 2300777.

[0078]

[10] Weiqian Kong, Xiaofan Zhang, Shuangshuang Liu, Yannan Zhou, Binbin Chang, Shouren Zhang, Hongbo Fan, and Baocheng Yang, N Doped Carbon Dot Modified WO3 Nanoflakes for Efficient Photoelectrochemical Water Oxidation, Adv. Mater. Interfaces 2019, 6, 1801653.

[0079] Example 5 Study on the catalytic degradation performance of organic pollutants

[0080] The method for investigating the degradation performance of simulated pollutants provided by the present invention is as follows:

[0081] Degradation experiments were carried out under simulated sunlight in a 45 mL rectangular quartz reactor containing a mixed solution of 5 mg / L NOR and 0.5 M Na2SO4 to evaluate the PEC performance of the photoanode. The sunlight light source and bias voltage were supported by a 300 W xenon lamp with an AM1.5G filter and a 0.9 V (vs. SHE) DC regulated power supply, respectively. The distance between the sunlight light source and the photoanode was fixed at 10 cm. Before the PEC degradation experiment, the NOR solution was stirred in the dark for 15 min to obtain the adsorption-desorption equilibrium between the photoanode and NOR. Subsequently, the PEC degradation experiment was started by turning on the light source and power supply. At regular intervals, a certain amount of NOR solution was drawn with a syringe and filtered with a 0.22 μm membrane filter. The obtained samples were used to determine the concentration of NOR in the solution by high performance liquid chromatography.

[0082] Example 1 Comparison of the performance of tungsten oxide thin film electrodes in photocatalysis, electrocatalysis and photoelectrocatalysis on pollutant NOR Figure 6 As shown, Figure 6 (a) and Figure 6 (b) It can be seen that photoelectrocatalysis has the best degradation ability; Figure 6 (c) It can be seen that there is almost no current response in electrocatalysis, which indicates that photoelectrocatalysis is mainly dominated by photocatalysis, and electrocatalysis plays an auxiliary role.

[0083] Example 1 Photoelectrocatalytic degradation activity of NOR by tungsten oxide thin film electrode under different voltages, such as Figure 7 As shown, the tungsten oxide thin film electrode can achieve 70% removal of NOR at a relatively low voltage of 0V, with the optimum voltage being 0.9V. It can degrade 100% of NOR within 60 minutes and can generate a photocurrent of 1.5mA / cm2.

[0084] Example 1 The results of the cyclic test of photoelectrocatalytic degradation of NOR by tungsten oxide thin film electrode are as follows Figure 8 As shown in the figure. After 5 cycles, NOR can still achieve 100% degradation within 60 minutes, and the photocurrent density has no obvious decrease. It can be seen that the tungsten oxide thin film electrode has good reusability and cycle stability.

[0085] Example 1 Photoelectrocatalytic removal effect of tungsten oxide thin film electrode on NOR under different electrolyte conditions Fig. 9 As shown, compared with electrolytes H2O, NaNO3, NaH2PO4, and Na2SO4, the catalyst has the highest degradation activity in the NaCl system and can degrade 100% of norfloxacin within 10 minutes, demonstrating its great potential and environmental application value in the remediation of organic pollutants in high-salt water environments.

Claims

1. A tungsten oxide thin film electrode material, characterized in that: The tungsten oxide thin film electrode material consists of a substrate and a tungsten oxide thin film covering the substrate; the substrate is FTO conductive glass; the thickness of the tungsten oxide thin film is 110-120 μm.

2. The tungsten oxide thin film electrode material according to claim 1, characterized in that: The oxide thin film electrode material is an n-type semiconductor, the band gap width of the oxide thin film electrode material is 2.54-2.62 eV, and the valence band position is 2.50-2.62V.

3. A method for preparing the tungsten oxide thin film electrode material according to claim 1 or 2, characterized in that: The steps include: S1: dissolving ammonium metatungstate in a solvent, adding citric acid aqueous solution and Triton X-100 thereto, and stirring to obtain a precursor solution; S2: drop the precursor solution onto the restricted area of ​​FTO conductive glass, dry it at room temperature and then calcine it to obtain tungsten oxide thin film electrode material.

4. The method for preparing a tungsten oxide thin film electrode material according to claim 3, characterized in that: The dosage ratio of ammonium metatungstate to citric acid aqueous solution in the precursor solution is 0.2 g:0.12 mL; the concentration of the citric acid aqueous solution is 0.1-5M.

5. The method for preparing a tungsten oxide thin film electrode material according to claim 3, characterized in that: The dosage ratio of ammonium metatungstate to Triton X-100 in the precursor solution is 0.2 g:10 μL.

6. The method for preparing a tungsten oxide thin film electrode material according to claim 3, characterized in that: The solvent is an ethanol aqueous solution, and the volume fraction of ethanol in the ethanol aqueous solution is 37.5%.

7. The method for preparing a tungsten oxide thin film electrode material according to claim 3, characterized in that: The amount of the precursor solution dropped into the FTO conductive glass confinement area in step S2 is 50 μL.

8. The method for preparing a tungsten oxide thin film electrode material according to claim 3, characterized in that: The calcination parameters in step S2 are as follows: heating to 550° C. at a heating rate of 1° C. / min and calcining for 2 h.

9. Use of the tungsten oxide thin film electrode material according to claim 1 or 2 in the degradation of organic pollutants in a high-salt water environment.

10. The use according to claim 9, characterized in that: The salt water concentration in the high salt water environment is 0.05-1M; and the organic pollutants include norfloxacin.

Citation Information

Patent Citations

  • A visible light-driven inverse opal photocatalyst, its preparation method, and its degradation and removal of organic pollutants in water.

    CN109529814B

  • Method for treating antibiotic wastewater using carbon nitride / tungsten trioxide / zinc sulfide dual Z-type composite photocatalyst

    CN114314735B

  • Method for preparing nano tungsten trioxide thin film

    CN101734866A

  • Preparation method of zinc-modified tungsten trioxide thin film photoelectrode

    CN103088381A

  • Super-hydrophilic self-cleaning antifogging composite film, and preparation method and application thereof

    CN104086092A